Kesulitan Dalam Memaknai Kesempurnaan Informasi Era Covid-19 - Tomy Michael (ADALAH, 2020)
Abstract:The existence of Covid-19 makes the meaning of human rights more sensitive and misinterpreted. There are several parties who try to underestimate Covid-19 by understanding it as Human Rights, so they are free to determine the fate of their health. The state in a pandemic condition is tasked with providing the best to the public such as health services, a sense of security, a stable economy, to survival. Social contract must be interpreted as part of the life of the state that prioritizes welfare. Therefore, information disclosure is needed and improved.Keywords: Human Rights; Information Abstrak:Adanya Covid-19 membuat makna hak asasi manusia menjadi lebih sensitif dan salah penafsiran. Ada beberapa pihak yang mencoba menyepelekan Covid-19 dengan memahaminya sebagai Hak Asasi Manusia, sehingga mereka bebas menentukan nasib kesehatannya. Negara dalam kondisi pandemi bertugas memberikan yang terbaik kepada masyarakat seperti pelayanan kesehatan, rasa aman, ekonomi yang stabil, hingga keberlangsungan hidup. Kontrak sosial harus dimaknai sebagai bagian dari kehidupan bernegara yang mengutamakan kesejahteraan. Oleh karenanya, keterbukaan informasi diperlukan dan ditingkatkan.Kata Kunci: Hak Asasi Manusia; Informasi